Vestibular approach for thyroid surgery: a comprehensive review - La Via, Luigi; Zanghì, Antonio; Cavallaro, Andrea; Di Vita, Maria; Maniaci, Antonino; Cocuzza, Salvatore; Cappellani, Alessandro; Di Majo, Simone (Frontiers in Surgery, 2024)
The transoral endoscopic thyroidectomy vestibular approach (TOETVA) is an innovative technique in thyroid surgery. This review compiles current research on TOETVA, covering its development, anatomical challenges, techniques, selection of suitable patients, results, complications, and future advancements. We performed a comprehensive literature review on PubMed, EMBASE, and Cochrane databases for articles published up to 15th March 2024. The search strategy included a combination of terms focused on "vestibular approach" and "thyroidectomy". The review underscores the necessity for preoperative planning and careful patient selection to reduce risks and enhance outcomes. It discusses the unique anatomical challenges of TOETVA, such as avoiding mental nerve damage and the complexities involved in creating a subplatysmal space. Outcomes of TOETVA, including surgical duration, complication rates, and recovery times, are compared favorably to traditional methods. The approach is particularly noted for high patient satisfaction and superior cosmetic results. Complications specific to TOETVA, like infection, bleeding, and potential harm to the recurrent laryngeal nerve, are recognized. Future research directions are discussed as well. In summary, TOETVA is a promising alternative for thyroidectomy with excellent cosmetic outcomes and patient satisfaction. Success relies on selective patient criteria, surgical expertise, and continuous research to refine the approach.